Novas perspectivas para o experimento da vela por meio de uma abordagem histórica - Bocato, Débora Cristina Curto da Costa (2016)
The aim of this work was to investigate the didactic potential of the historical approach of the combustion in the first year students of an undergraduate Chemistry course. The experimental observation of a candle proposed in high school and in introductory courses of some higher education courses in Natural Sciences is usually adopted for the student to know and exercise the "scientific method". This procedure strengthens the naive notion that knowledge is acquired from the empirical-inductive method, which postulates that knowledge begins with observation, besides consolidating a linear view, ahistorical and progressive science. We propose a historical approach of this experiment, using it for presentation and discussion of combustion theories of Carl Scheele, Joseph Priestley and Antoine Lavoisier, who faced the eighteenth century. First year students of a Public University of Paraná State in Brazil performed the experiment in its classic mode and subsequently discussed about the wrong conclusions that this experiment can bring. Then they conducted targeted activities based on studies focused on the history of chemistry, particularly the work of the aforementioned scholars. The historical approach of the episodes of the combustion enabled students to meaningful learning of scientific knowledge. They had access to the process of construction of theories and might perceive science as a social production, and the activity carried out allowed the scholars began to take ownership of a new epistemological model, in which are present the non-neutrality and conflicts inherent to the development of new theories. In this sense, they have come to understand the nonlinear process of knowledge production as well as the theoretical debates involved and had the opportunity to perfect their designs, building a more critical, social and historical view about Science and how it works.